Palaeomagnetism and Magnetic Polarity Zones in the Jurassic Dufek Intrusion, Pensacola Mountains, Antarctica - Beck, Myrl E. (Geophysical Journal International, 1972)
The Dufek intrusion, of the Pensacola Mountains, Antarctica, is a stratiform mafic complex consisting of layered gabbro with subordinate amounts of anorthosite, pyroxenite and granophyre, forming a little-deformed sheetlike intrusion at least 6 km thick. Its age is estimated as Jurassic. Of 183 oriented hand samples originally collected from the intrusion for palaeomagnetic studies, 98 proved to be magnetically stable, including 61 samples of normal polarity, 30 of reversed polarity, and seven that are intermediate. The distribution of polarities within the intrusion makes it impossible to rule out either self-reversal or geomagnetic field reversal as the cause of the dual magnetic polarities; possibly both processes were operative. Both intensity of remanent magnetization and magnetic susceptibility generally increase with stratigraphic height in the intrusion. Mean directions of remanent magnetization for the two polarity groups are very nearly antiparallel, and when combined yield a south palaeomagnetic pole at 56·5° S., 168° W., for the Dufek intrusion. This pole lies near poles previously reported for the Jurassic Ferrar dolerite. Available data are not sufficient to define the behaviour of the pole in relation to Antarctica during most of the Mesozoic. Palaeomagnetic evidence tends to support the proposition that West and East Antarctica were independent entities in pre-Tertiary time, and to suggest that there has been significent Tertiary movement of crustal blocks within West Antarctica.